ASPEK RENTABILITAS, LIKUIDITAS DAN SOLVABILITAS PADA KINERJA KEUANGAN PT. PERKEBUNAN NUSANTARA III SUMATERA UTARA PERIODE 2012-2014 - Ramadona Simbolon (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
This study focused on financial performance of PT. Perkebunan Nusantara III (Persero) in the period 2012-2014, before the company was appointed as a chief of holding company of State-Owned Enterprises (BUMN). This appointed holding company caused to raise questions related to the condition of the company such as related to management, production and finance; whether the company belonged to healthy company. Therefore, this research was conducted by referring to the Decree of the Minister of Finance of the Republic of Indonesia No. 826/KMK.013/1992 which described the standardization of healthy company in terms of profitability, liquidity and solvency. This research was a qualitative descriptive research with data collection from both primary and secondary sources in the form of documents. Analyzing data was performed on these documents by detailing, comparing and describing them for conclusions. The results of this study indicated that the overall financial performance level of the company was unhealthy based on the average for three years, from 2012 to 2014 by considering to the Decree of the Minister of Finance of RI. No. 826 KMK.013/1992 in terms of profitability, liquidity and solvency. The average achievement rate over the last three years was 64.52%, where the achievement was less than 90. This might be due to several internal factors such as non-business costs or lack of power in paying corporate liabilities. Therefore for the next period the company must pay attention to these factors in order to achieve company goals in accordance with expectations.